Planning for the Development of Education Quality at SDN 006 Pasir Belengkong - Thoriq, Alfan; Zakiyah, Retno Himma; Suzetasari, Melisa Vania; Silawati, Silawati; Ramadhan, Andriawan Fajar; Hidayati, Dian (Universitas Muhammadiyah Surakarta, 2024)
Educational quality development planning is an effort made to improve the quality of education delivery in academic units. Analysis of educational quality development planning is needed to improve the quality of schools accredited C through SWOT analysis. This study aims to determine the planning and development of quality. Education in schools accredited C. Qualitative research method with a case study approach. This study's subjects consisted of the SDN 006 Pasir Belengkong principal. This research was implemented in December 2023, and it took place at SDN 006 Pasir Belengkong. The data collection methods used by the researcher were interviews, observation, and documentation. The results of the study indicate that improving the quality of education at SDN 006 Pasir Belengkong can be done through branding of cultural schools, improving the quality of educational staff, building networks of cooperation with educational investors, optimizing support and involvement of alums and the community, and maximizing the use of school operational assistance or BOS received from the government or donors to improve the existing management and infrastructure systems.